Analysis of constructive effect and soil-structure interaction in tall building projects with shallow foundations on sandy soils - Marques,Olivia Catelan (2021)
Abstract: The influence of incremental constructive effects (IE) and soil-structure interaction (SSI) on high-rise buildings of reinforced concrete with shallow foundations on sandy soils were analyzed. IE and SSI evaluations were carried out by the parameters of global instability, maximum horizontal displacements, foundation loads, and settlements of a symmetrical and non-symmetrical plant of a 23-storey building For the analysis of the IE, the variation of the modulus of elasticity was considered over time along with the phases of application of loads in the building. For ISS analysis, the continuous medium was considered, and the calculation model considers a multi-spring-mass system under the foundation of the building. The results show a significant redistribution in the foundation efforts and suggest that a failure in considering these effects along with the structure can lead to projects that do not meet the standard specifications regarding stability parameters and overall structure displacements.